2019
DOI: 10.1111/ane.13114
|View full text |Cite
|
Sign up to set email alerts
|

Subjective working and declarative memory in dementia and normal aging

Abstract: Objective Subjective memory complaints are common in both elderly individuals and patients with dementia. This study investigated the power of subjective memory, divided into declarative and working memory, to differentiate between patients with dementia and normal elderly individuals. Method Two groups of participants, patients with dementia (n = 117) and normal elderly individuals (n = 117), individually matched with regard to age, gender, and education. All subjects had participated in the third wave of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…A second implication would be that to learn about a person's episodic/semantic memory, you should ask about the person's ratings of present activity and most recent events. In an earlier paper [23], for example, we showed that MMQ outcomes could be used to differentiate between demented and healthy older individuals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A second implication would be that to learn about a person's episodic/semantic memory, you should ask about the person's ratings of present activity and most recent events. In an earlier paper [23], for example, we showed that MMQ outcomes could be used to differentiate between demented and healthy older individuals.…”
Section: Discussionmentioning
confidence: 97%
“…The Meta-Memory Questionnaire (MMQ) was chosen as a test of subjective memory in the present study, because it has been used previously in the Nordic countries [21][22][23][24][25], the internal structure has been investigated and found to be multi-dimensional [20], because there is no international standard of subjective memory test to rely on [17], and because this nine item questionnaire was used in the third wave of the North-Trøndelag Health survey (HUNT3) [26]. Interestingly, six among the nine items in the MMQ are included in the list of the 10 most common items in other questionnaires that assess subjective memory as reported by Rabin and associates [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing the need to include tools (self-reports) that assess more executive processes such as working memory rather than declarative memory processes also advocated for the relevance of multiple-cognitive-domain screening compared to classical unidimensional cognitive assessments [ 52 ]. Thus, one of the limitations in the analyzed studies was the generalization in neurocognitive assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that implicit memory remains relatively stable over the adult lifespan (Lalla, Tarder-Stoll, Hasher, & Duncan, 2022) whereas others have reported age-related decline (Ward, Berry, Shanks, Moller, & Czsiser, 2020). Age effects on implicit memory can be influenced by factors such as attention and depth of processing (Almkvist, Bosnes, Bosnes, & Stordal, 2019).…”
Section: Cognitive Performance Of Older Adults: Understanding and Imp...mentioning
confidence: 99%